2012
DOI: 10.1111/jfd.12012
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of sample collection methods (organs vs swabs) for Tasmanian salmon reovirus detection in farmed Atlantic salmon, Salmo salar L.

Abstract: The use of swabs relative to organs as a sample collection method for the detection of Tasmanian salmon reovirus (TSRV) in farmed Tasmanian Atlantic salmon, Salmo salar L., was evaluated by RT-qPCR. Evaluation of individual and pooled sample collection (organs vs swabs) was carried out to determine the sensitivity of the collection methods and the effect of pooling of samples for the detection of TSRV. Detection of TSRV in individual samples was as sensitive when organs were sampled compared to swabs, and in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Kumar et al (2015) explained that the occurrence of a new serotype may limit vaccine efficacy. In addition, even though the vaccination has managed to protect fish to certain degrees against yersiniosis, it has been argued that the previous approach was unable to prevent the establishment of asymptomatic carriers within surviving populations of Tasmanian Atlantic salmon (Ghosh et al, 2016; Tobback et al, 2007; Zainathan, 2012). Thus, new prevention methods are urgently required to prevent or limit infection and reduce economic losses for salmonid production.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al (2015) explained that the occurrence of a new serotype may limit vaccine efficacy. In addition, even though the vaccination has managed to protect fish to certain degrees against yersiniosis, it has been argued that the previous approach was unable to prevent the establishment of asymptomatic carriers within surviving populations of Tasmanian Atlantic salmon (Ghosh et al, 2016; Tobback et al, 2007; Zainathan, 2012). Thus, new prevention methods are urgently required to prevent or limit infection and reduce economic losses for salmonid production.…”
Section: Introductionmentioning
confidence: 99%
“…In DPIPWE‐Tasmania, further application of RT‐qPCR was evident in the development of a rigorous and defined sample collection method for TSRV (Zainathan et al . ). The use of RT‐qPCR in this study showed that the limit of detection was down to 1.94 × 10 4 molecules μL −1 with initial viral copy numbers of 1.94 × 10 7 molecules μL −1 .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, non-lethal sampling techniques such as the swab method are highly recommended. Zainathan et al [44] evaluated the use of swabs and organs to detect the Tasmanian salmon reovirus. The results demonstrated that swabs were as effective as organ samples.…”
Section: Discussionmentioning
confidence: 99%